1987
DOI: 10.1113/jphysiol.1987.sp016876
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the jejunal migrating motor complex by gastric distension and feeding in the dog.

Abstract: SUMMARY1. The jejunal motor response to gastric distension has been quantified in the conscious dog and compared with that of feeding in order to determine the role of the physical bulk of a meal in the conversion from fasted to fed motor activity.2. In six dogs gastric distension abolished the cyclical migrating motor complex (m.m.c.) and evoked a pattern of continuous irregular jejunal motility similar to that seen postprandially, but only after a latency of 21 5±2'7 min compared to that of 7.1 + 1P2 min for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…Infusion of hyperosmolar solutions and intake of meals are known occasionally to initiate a burst of activity at the slow wave frequency. '*-'' Bull et al observed a burst of regular contractions in 18 The present study shows that the motor reponse to caloric meals depends on phase of MMC at food intake, suggesting that this enteric rhythm continues to cycle during the postprandial period, even if the contractile pattern of MMC is mainly concealed by food-induced irregular contractile activity. This modified concept of postprandial motility allows previous and recent observations to be e~p l a i n e d .…”
Section: Discussionsupporting
confidence: 59%
“…Infusion of hyperosmolar solutions and intake of meals are known occasionally to initiate a burst of activity at the slow wave frequency. '*-'' Bull et al observed a burst of regular contractions in 18 The present study shows that the motor reponse to caloric meals depends on phase of MMC at food intake, suggesting that this enteric rhythm continues to cycle during the postprandial period, even if the contractile pattern of MMC is mainly concealed by food-induced irregular contractile activity. This modified concept of postprandial motility allows previous and recent observations to be e~p l a i n e d .…”
Section: Discussionsupporting
confidence: 59%
“…All dogs were given post-operative analgesic therapy (buprenorphine, 0-02 mg/kg) for 24 h and a 5-day course of antibiotics (amoxycillin trihydrate, 8 mg/kg). The details of the cannulae and the care of the animals has been published previously (Bull, Grundy & Scratcherd, 1987).…”
Section: Surgerymentioning
confidence: 99%
“…Details of the surgery, post-operative care and animal husbandry have been described previously (Bull, Grundy & Scratcherd, 1987;Grundy et al 1989). …”
Section: Methodsmentioning
confidence: 99%
“…The experiments were performed on six unanaesthetized healthy dogs (weight 20-25 kg) which had been prepared with a divided stomach, corporal and antral fistulae and a gastrojejunostomy. Details of the surgery, post-operative care and animal husbandry have been described previously (Bull, Grundy & Scratcherd, 1987;Grundy et al 1989).…”
Section: Methodsmentioning
confidence: 99%